The association between peri-dialytic pulse wave velocity measurements and hemodialysis patient mortality - Surachet Vongsanim (2020)
© 2020 International Society for Hemodialysis Introduction: Arterial stiffness in the general population is an independent prognostic factor for cardiovascular mortality, and can be measured noninvasively by pulse wave velocity (PWV). PWV is increased in hemodialysis (HD) patients, but the prognostic additional value remains debatable, with variable results reported. We wished to review whether increased PWV was associated with mortality in our HD patients. Methods: Aortic pulse wave velocity (PWVao) was measured peridialytic using an oscillograph technique (Arteriograph TensioMed, Hungary), in a cohort of HD patients in 2012. Findings: Three hundred and eighty-three HD patients, 238 (62.1%) male, median age 67.7 (54.2–78.0) years, 163 (42.6%) diabetic, Charlson comorbidity score 7 (5–9) and PWVao 8.9 (7.4–11.2) m/s were studied. Two hundred and twenty-nine deaths occurred during a median 61.1-month follow-up. PWVao was associated with all-cause mortality in unadjusted models (odds ratio [OR] for PWVao as a continuous variable 1.084, 95% confidence limits [CL] 1.046–1.124), P < 0.001, and for patients with PWVao>10 m/s (OR 1.61, CL 1.240–2.098, P < 0.001), but not after adjusting for clinical confounders (OR 1.024, CL 0.987–1.063, P = 0.208), whereas age (OR 1.049, CL 1.038–1.060, P < 0.001), and Charlson comorbidity (OR 1.131, CL1.065–1.201, P < 0.001) remained significantly associated with mortality. Discussion: Although our HD patients with an increased PWVao had greater all-cause mortality, after adjustment for age and comorbidity, the prognostic value of a single PWVao measurement was no longer an independent prognostic factor for mortality. Future studies are required to determine whether changes in PWV offer additional prognostic value for HD patients.